Life in poetry - Wilder, Josephine Hannah (My University, 1898)
Introduction: In every one there is a spirit which sees beneath the surface. In every one there is a touch of the artist and poet. To but a few, however, is given the power to put the ideal picture on canvas, or to make the picture clear to other eyes in poetic utterance, beautiful with though and imagination. The poet must be an artist. He must interpret life in its artistic forms. Bare realism possesses no poetry. It is not real living when life is manifest in mere forms. The more we live by conventional rule, the more life becomes simply existence. So it is in poetry. If the poet makes life and nature expressionless or conventional, it is not life, it is not nature, and it is only an invitation. The real artist-poet compels the reader to share his admiration for his characters and his love for nature. He introduces and describes both character and nature so they can be recognized if met. He fills the reader with a longing to know more about Nature, to become better acquainted with her personally.
Citation: Wilder, Josephine Hannah. Life in poetry. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Life; Poetry; Nature; Artist; Theses; Manuscripts (documents)